Silent Arteriovenous Malformation, Loud Movements: A Dyskinetic Puzzle Resolved by Staged Craniotomy and Immediate Globus Pallidus Internus Deep Brain Stimulation - Gannison, Lalithambigai; Muthusamy, Kalai Arasu (Nepal Journal of Neuroscience, 2026)
Background: Tardive dyskinesia is a debilitating hyperkinetic movement disorder characterized by repetitive involuntary movements involving the orofacial musculature. The disorder most commonly arises following exposure to dopamine receptor–blocking medications and reflects dysfunction within cortico-basal ganglia-thalamocortical motor circuits¹. Structural brain lesions may further destabilize motor network function and contribute to abnormal movement patterns. Cerebral arteriovenous malformations (AVMs) are congenital vascular anomalies that typically present with intracranial hemorrhage, seizures, headaches, or progressive neurological deficits². Movement disorders associated with AVMs are rare.Case Description: We report a case of severe refractory oro-buccal dyskinesia in a patient with a cerebral AVM and seizure disorder. Neuroimaging demonstrated a left posterior temporal arteriovenous malformation located near the temporoparietal junction. Despite withdrawal of the offending medication and trials of tetrabenazine and botulinum toxin injections, the dyskinesia persisted. The patient underwent microsurgical AVM excision, which resulted in angiographic cure and seizure control but did not resolve the abnormal movements. Because of persistent disabling dyskinesia, the patient subsequently underwent bilateral globus pallidus internus deep brain stimulation (GPi-DBS). Intraoperative microelectrode recordings confirmed appropriate pallidal neuronal activity. An implantable pulse generator was implanted during the same procedure and stimulation was activated immediately in the recovery period, resulting in rapid suppression of dyskinetic movements.Conclusion: This case highlights the complex interaction between structural cerebrovascular pathology and dysfunctional basal ganglia circuitry. Successful treatment required a staged neurosurgical strategy combining vascular and functional neurosurgery. Immediate activation of pallidal stimulation produced dramatic clinical improvement and demonstrates the therapeutic role of neuromodulation in refractory dyskinetic disorders.